(untitled) (Scientific journal of the Fergana State University, 2026)
This article comprehensively studies the dynamics of interethnic relations in the Republic of Uzbekistan, paying special attention to the historical evolution and current state of relations between fraternal nations and the peoples of Uzbekistan (specifically, in the case of the Fergana region). The study examines the specific features of socio-cultural relations and their impact on interethnic harmony. The stages of developing friendly and cooperative relations between Tajikistan, Kyrgyzstan, Uzbekistan, as well as the economic and cultural integration processes, are considered. The role of bilateral agreements, cooperation projects and interpersonal relationships in strengthening interethnic harmony is considered. The study aims first of all to assess the future of Uzbek-Tajik and Kyrgyz relations in modern geopolitical contexts, highlighting the interaction of regional security, migration policy, and cultural exchange. The results show that relations based on strong historical cooperation are being strengthened economically and culturally, strengthening mutual understanding and respect between peoples.